Green Synthesis of ZnO Nanoparticles using Abelmoschus esculenthus L. Fruit Extract: Antioxidant, Photoprotective, Anti-inflammatory, and Antibacterial Studies - Christina Astutiningsih; Tias Eka Rahmawati; Nanik Astutik Rahman; Meri Meri (Journal of Multidisciplinary Applied Natural Science, 2024)
Nanoparticles are extensively studied for their promising biological properties. In this study, the fruit extract of Abelmoschus esculenthus L. was used as a chelating agent for the synthesis of zinc oxide nanoparticles (ZnOPs-AE) using a zinc acetate solution. The prepared ZnOPs-AE were identified and characterized using UV-vis spectroscopy, Fourier-transformed infrared spectroscopy (FTIR), particle size analyzer (PSA), scanning electron microscopy (SEM), and energy dispersive spectrum (EDS). The green synthesized ZnOPs-AE were evaluated for their antioxidant, photoprotective, anti-inflammatory, and antibacterial activities. The synthesized nanoparticles showed an intensity peak at 370 nm in the UV-vis spectrum. The FTIR result shows the presence of O-H, C=O, C-O, C-OH, and C=C chelating functional groups on the surface of nanoparticles. The size of ZnOPs-AE was determined using a PSA with particle size distribution of 102.2 nm. The ZnOPs-AE were shown to be spherical by SEM analysis and composition was 82.11% and 14.79% for Zn and O, respectively. The antioxidant properties of ZnOPs-AE showed significant antioxidant potential in DPPH, ABTS, and FRAP assays compared to the quercetin standard. The photoprotection activity test showed a SPF value of 19.63, the percentage of erythema transmission was 5.98%, and the percentage of pigmentation transmission was 5.62%. The ZnOPs-AE showed good anti-inflammatory with the synthesized nanoparticle performing activity between positive control and the fruit extract of Abelmoschus esculenthus L. Also, the ZnOPs-AE exhibited good antibacterial activity against Staphylococcus aureus (20.78 mm) and Pseudomonas aeruginosae (11.13 mm). Overall, the results highlight the effectiveness and potential of ZnOPs-AE for biological application.